Webster's new world children's dictionary - Agnes, Michael (Wiley, 1999)
With hundreds of new entries, maps, photos, illustrations, and an all-new look, Webster's New World Children's Dictionary, Second Edition now offers even more of the unique features and qualities most sought by parents and educators. Developed in collaboration with leading educators and textbook publishers, this top-quality dictionary is written and designed specifically for children ages 8 to 11. Its more than 33,000 entries are based on contemporary children's literature and the writings of children themselves. Definitions are clear and accurate, with thousands of up-to-date example sentences that help children put meanings into real-life context. Over 750 specially commissioned, full-color photographs, illustrations, and maps aid understanding and add appeal. Word histories, synonym studies, spelling tips, and a children's thesaurus help build important reading, writing, and spelling skills. Plus, a special illustrated reference section introduces children to key U.S. and world information.Tested nationally in focus groups, this dictionary has received the highest approval rating of all currently available children's dictionaries. Now completely revised and updated in both look and content, it continues to be the only children's dictionary that offers all of these features